2010
DOI: 10.1038/nrgastro.2010.4
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of IBS: role of inflammation, immunity and neuroimmune interactions

Abstract: IBS is one of the most common functional gastrointestinal disorders worldwide and is thought to be the result of disturbed neural function along the brain-gut axis. The mechanisms behind this disturbance are not clear, but important roles for low-grade inflammation and immunological alterations in the development of symptoms compatible with IBS have become evident. The development of long-standing gastrointestinal symptoms after infectious gastroenteritis and patients with IBD in remission frequently having fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
448
1
17

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 532 publications
(478 citation statements)
references
References 113 publications
12
448
1
17
Order By: Relevance
“…Th e gastrointestinal (GI) tract contains extensive immune and nervous systems (outlined in Figure 1 ), and alterations in the immune system are increasingly implicated in the pathogenesis of IBS ( 2 ). Th is was fi rst observed in patients that attributed their symptoms to prior exposure to a GI pathogen, termed post-infectious IBS, but more recently has also been shown in other IBS cohorts ( 2,3 ). Surprisingly, little is known of how changes in the immune function aff ect the nerve function in IBS.…”
Section: Introductionmentioning
confidence: 99%
“…Th e gastrointestinal (GI) tract contains extensive immune and nervous systems (outlined in Figure 1 ), and alterations in the immune system are increasingly implicated in the pathogenesis of IBS ( 2 ). Th is was fi rst observed in patients that attributed their symptoms to prior exposure to a GI pathogen, termed post-infectious IBS, but more recently has also been shown in other IBS cohorts ( 2,3 ). Surprisingly, little is known of how changes in the immune function aff ect the nerve function in IBS.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is widely viewed as a disorder caused by a dysregulation of the complex interactions that exist along the brain-gut axis (Grenham et al 2011). Altered hypothalamic-pituitary-adrenal (HPA) axis function (Mayer, 2000), autonomic dysfunction (Tillisch et al 2005), immune activation (Ohman & Simren, 2010) and heightened central pain sensitivity (Mayer et al 2009) are considered key pathophysiological features related to abnormal brain-gut interactions in IBS. Observational studies have identified that stressors, such as early life trauma (Chitkara et al 2008) or chronic stressful life events experienced in adolescence or adulthood (Blanchard et al 2008), are major risk factors for IBS.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, IBS is increasingly viewed as a low grade inflammatory disorder, 3 and attentions have been focused on the roles of mast cells (MCs) in the gut wall, accounting for the close relations of MCs with major intestinal functions, such as epithelial secretion, epithelial permeability, blood flow, neuroimmune interactions, visceral sensation, and peristalsis. 4 MCs hyperplasia and activation lead to abnormal gastrointestinal sensitivity, motility, and secretion, which in turn contribute to the hallmark symptoms of IBS-abdominal pain and/or discomfort, bloating, and abnormal bowel function (diarrhea and/or constipation).…”
Section: Introductionmentioning
confidence: 99%